Tren Kata Kunci Artikel Anuva: Jurnal Kajian Budaya, Perpustakaan dan Informasi - Hijrana, Hijrana (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2024)
In a scientific work such as a journal article, the writing of keywords is an essential part of a scholarly publication. They are usually used to represent concepts or ideas in the writing. By using keywords, authors can reach a wider readership, and the information needed matches the readers' desires. The study of keyword trends in the Anuva journal aims to map the keywords in the articles, enabling more specific information retrieval. This research employs a qualitative descriptive analysis of data downloaded from the Anuva website (https://ejournal2.undip.ac.id/index.php/Anuva/), then processed using Microsoft Excel, and the data is displayed in tabular form and analyzed to produce conclusions that can generally be narrated in tables. The data used in the research spans from 2017 to 2022. The results show that Anuva has published 227 articles from 2017 to 2022. The highest number of articles was published in 2021, with 54 articles, and the lowest was in 2017, with 174 articles, with a total of 839 keywords. The most frequently used keywords are